2008
DOI: 10.1083/jcb.200804140
|View full text |Cite
|
Sign up to set email alerts
|

Rab-coupling protein coordinates recycling of α5β1 integrin and EGFR1 to promote cell migration in 3D microenvironments

Abstract: Here we show that blocking the adhesive function of αvβ3 integrin with soluble RGD ligands, such as osteopontin or cilengitide, promoted association of Rab-coupling protein (RCP) with α5β1 integrin and drove RCP-dependent recycling of α5β1 to the plasma membrane and its mobilization to dynamic ruffling protrusions at the cell front. These RCP-driven changes in α5β1 trafficking led to acquisition of rapid/random movement on two-dimensional substrates and to a marked increase in fibronectin-dependent migration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
398
3
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(430 citation statements)
references
References 54 publications
15
398
3
5
Order By: Relevance
“…The effect of annexin A2 on EGFR endocytosis is linked to activation of the actin-severing protein cofilin establishing annexin A2 as a mediator of EGFR endocytic trafficking and signaling in breast cancer cells via regulation of cofilin activation [40]. Furthermore, the Rab11 effector Rab-coupling protein (RCP) has pro-invasive effects by forming a complex with the integrin a5b1 and EGFR1 and by coordinating their recycling [41]. EGFR-dependent signaling likely occurs partly from the plasma membrane, leading to the activation of PKB/Akt via phosphoinositide-3-kinase (PI3K), and partly from late endosomal compartments, resulting in the activation of the Ras-MEK-ERK axis (see references in [41]).…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 99%
See 3 more Smart Citations
“…The effect of annexin A2 on EGFR endocytosis is linked to activation of the actin-severing protein cofilin establishing annexin A2 as a mediator of EGFR endocytic trafficking and signaling in breast cancer cells via regulation of cofilin activation [40]. Furthermore, the Rab11 effector Rab-coupling protein (RCP) has pro-invasive effects by forming a complex with the integrin a5b1 and EGFR1 and by coordinating their recycling [41]. EGFR-dependent signaling likely occurs partly from the plasma membrane, leading to the activation of PKB/Akt via phosphoinositide-3-kinase (PI3K), and partly from late endosomal compartments, resulting in the activation of the Ras-MEK-ERK axis (see references in [41]).…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 99%
“…Furthermore, the Rab11 effector Rab-coupling protein (RCP) has pro-invasive effects by forming a complex with the integrin a5b1 and EGFR1 and by coordinating their recycling [41]. EGFR-dependent signaling likely occurs partly from the plasma membrane, leading to the activation of PKB/Akt via phosphoinositide-3-kinase (PI3K), and partly from late endosomal compartments, resulting in the activation of the Ras-MEK-ERK axis (see references in [41]). RCP-dependent recycling might keep EGFR from efficiently reaching late endosomes thereby promoting pro-invasive PKB/Akt signaling [41].…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 99%
See 2 more Smart Citations
“…In a more recent study, the same authors [Caswell et al, 2008] showed that an effector of the Rab family proteins, Rab11 family interacting protein 1 (Rab11-FIP1), or Rab-coupling protein (RCP), may be another mediator of Rab25's effect on a5b1-integrin traffic and cell migration. Blocking of avb3-mediated cell adhesion with soluble ligands (such as osteopontin or cilengtide) promoted association of RCP with a5b1-integrin, and the latter's recycling to the plasma membrane as well as its mobilization to dynamic protrusions at the cell front.…”
Section: Rabs Integrin Traffic and Cancer Cell Adhesion/migrationmentioning
confidence: 99%